Structural characteristics of sulfated polysaccharides from Sargassum horneri and immune-enhancing activity of polysaccharides combined with lactic acid bacteria. Issue 15 (14th July 2022) - Kim, Young-Sang; Hwang, Jin; Lee, Sang Gil; Jo, Hee Young; Oh, Myung Jin; Liyanage, N. M.; Je, Jun-Geon; An, Hyun Joo; Jeon, You-Jin
Abstract : Sargassum horneri (SH), a marine brown alga, is known to contain a variety of bioactive ingredients and previous studies reported sulfated polysaccharides in SH as a potential candidate for a functional ingredient. Abstract : Sargassum horneri (SH), a marine brown alga, is known to contain a variety of bioactive ingredients and previous studies reported sulfated polysaccharides in SH as a potential candidate for a functional ingredient. However, immune-enhancing activity combined with Lactobacillus plantarum (LAB) is not yet studied. In the present study, we attempted to characterize sulfated polysaccharides (SHCPs) in SH by MALDI-TOF/TOF mass spectrometry and evaluate their immune-enhancing effect on macrophage cells. The main residue of SHCPs in SH is 2-sulfated 1, 4-linked l -fucose and this epitope combined with LAB shows immune enhancement properties through cytokine production at the cellular level and increases the population of lymphocytes and myelomonocytes in the adult zebrafish kidney. These results indicate that SHCPs, along with LAB, have potent immune-enhancing activity and may be utilized as a potential immunomodulatory ingredient.